A comprehensive overview of FFRG and IHCC allograft cartilages in revision rhinoplasty: a systematic review - Mahtab Hosseini; Seied Omid Keyhan (Head & Face Medicine)
Abstract Background This study aims to compare the complications and satisfaction associated with favorable allografts, Fresh Frozen Rib Graft (FFRG) and Irradiated Homologous Costal Cartilage (IHCC), in revision rhinoplasty. Methods The PRISMA guidelines were adhered to in the conduct of this systematic review. No limitations were applied to the types of studies included. Studies in English were selected without any time limitations. Five databases, PubMed/Medline, Cochrane Library, Embase, Scopus, Google Scholar, and also, the reference lists of included studies were searched. The ROBINS-I was employed for risk of bias assessment. Patients who underwent revision rhinoplasty utilizing allografts (FFRG and IHCC) were considered. Results The initial search yielded a total of 503 studies. After duplicate removal and paper screening, 7 studies were included. A total of 406 patients for FFRG and 66 patients for IHCC who underwent revision rhinoplasty with the use of FFRG and IHCC were incorporated. Various complications were assessed, including warping, infective/noninfective resorption, infection, extrusion/displacement, and other less common occurrences. The overall complication rates were 9.25% and 15.7% for FFRG and IHCC, respectively. The main complication associated with the two was infection. Notably, both FFRG and IHCC demonstrated significant improvements in patient satisfaction following revision surgery across all subjected studies. Conclusion Based on this review, FFRGs present a lower rate of complications in comparison with IHCCs. However, the biocompatibility makes the autologous rib cartilage the gold standard graft, but in case of donor site limitations to harvesting, FFRG and IHCC would be a safe and reliable alternative.